SOCIO-ECONOMIC DEVELOPMENT OF CRIMEA AND ITS IMPACT ON THE TAX POTENTIAL OF THE REGION - Tatiana Zhuravleva (Krymskij Naučnyj Vestnik, 2015)
In this article the analysis of the main macroeconomic indicators of development of the Autonomous Republic of Crimea from the standpoint of assessment of the tax potential of this area and predict the possible income taxes. Studied industrial structure development of this area as a part of Ukraine, and after joining Russia, analyzed the current situation with profitable and unprofitable enterprises of the Crimea in comparison with the national data.